Biopsychosocial needs and perceptions on senior day care of the functional elderly in the Village of Dayap in Calauan, Laguna, Philippines - Torres, Renato V. (2011)
The Senior Day Care is necessarily satisfy the biopsychosocial need of the functional elderly. The study aims to determine the unmet biopsychosocial needs and perceptions on senior day care of 100 functional elderly, aged 60 years and above, in the village of Dayap in Calauan, Laguna.

The descriptive study was aided by interviews and questionnaires. Socio-demographic and perception data were processed and analyzed using descriptive statistics, Marascuilo procedure, Pearson's correlation, and Monte Carlo method.

Majority of the respondents, with ages ranging from 60 to 89, were married and were earning for their living. The respondents' level of awareness on Senior Day Care was low at 32% but their willingness to participate was high at 71% after the concept was explained. Major reasons for their willingness to join were their desire to be productive, active, healthy, and strong. Identified reasons for not taking part in the Senior Day Care were lack of time and preference to stay at home.

The culturally acceptable senior day care services needed were medical screening, nutritional counseling, livelihood, health education, and physical fitness. Psychological counseling, socialization, and recreational arts and crafts were the least preferred services.
Keywords: Elder care; Older people -- Calauan (Laguna)